TOPICAL ISSUES OF COPYRIGHT IN THE ACTIVITIES OF THE LIBRARY SERVICE (Scientific journal of the Fergana State University, 2023)
The article discusses the problems of copyright in library activities, legislation in this area and their practical application, recommendations and guidelines for copyright protection. It also describes the conditions for the use of library activities for people with disabilities, the content of international documents on free access to books.